EBV Infection and Its Regulated Metabolic Reprogramming in Nasopharyngeal Tumorigenesis - Yang, Tingting; You, Chanping; Meng, Shuhui; Lai, Zhengquan; Ai, Weipeng; Zhang, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Viral oncogenes may drive cellular metabolic reprogramming to modulate the normal epithelia cell malignant transformation. Understanding the viral oncogene–mediated signaling transduction dysregulation that involves in metabolic reprogramming may provide new therapeutic targets for virus-associated cancer treatment. Latent EBV infection and expression of viral oncogenes, including latent membrane proteins 1 and 2 (LMP1/2), and EBV-encoded BamH I-A rightward transcripts (BART) microRNAs (miR-BARTs), have been demonstrated to play fundamental roles in altering host cell metabolism to support nasopharyngeal carcinoma (NPC) pathogenesis. Yet, how do EBV infection and its encoded oncogenes facilitated the metabolic shifting and their roles in NPC carcinogenesis remains unclear. In this review, we will focus on delineating how EBV infection and its encoded oncoproteins altered the metabolic reprograming of infected cells to support their malignances. Furthermore, based on the understanding of the host’s metabolic signaling alterations induced by EBV, we will provide a new perspective on the interplay between EBV infection and these metabolic pathways and offering a potential therapeutic intervention strategy in the treatment of EBV-associated malignant diseases.